2008
DOI: 10.1089/scd.2007.0153
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Factors–Mediated Immunomodulatory Effects of Canine Adipose Tissue–Derived Mesenchymal Stem Cells

Abstract: Adipose tissue-derived mesenchymal stem cells (AD-MSCs), which can differentiate into several lineages, have immunomodulatory properties similar to those of bone marrow-derived MSCs. However, the specific mechanism by which the immunomodulatory effect of MSCs occurs is not clear. In this study, we isolated canine AD-MSCs (cAD-MSCs) and induced their development into adipocyte, osteocyte, and neuron-like cells. We then investigated their phenotype and cytokine expression to determine whether they were able to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
158
3
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 58 publications
(88 reference statements)
14
158
3
4
Order By: Relevance
“…While it remains controversial whether cell-cell contact is required for ADSC's immunosuppressive effects [29][30][31], several studies have demonstrated the importance of soluble factors, among which the most frequently identified being prostaglandin E2 (PGE2) [31,[38][39][40][41]. Specifically, inhibition of PGE2 by indomethacine effectively abolished ADSC's immunosuppressive effects.…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culture mentioning
confidence: 99%
See 1 more Smart Citation
“…While it remains controversial whether cell-cell contact is required for ADSC's immunosuppressive effects [29][30][31], several studies have demonstrated the importance of soluble factors, among which the most frequently identified being prostaglandin E2 (PGE2) [31,[38][39][40][41]. Specifically, inhibition of PGE2 by indomethacine effectively abolished ADSC's immunosuppressive effects.…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culture mentioning
confidence: 99%
“…Specifically, inhibition of PGE2 by indomethacine effectively abolished ADSC's immunosuppressive effects. In addition, specific inhibition of indoleamine 2, 3 dioxygenase [39] or neutralization of leukemia inhibitory factor [42] has also been shown to abolish ADSC's immunosuppressive effects. Further, ADSC's immunosuppressive activity appears to be mediated through an interleukin-6 (IL-6)-dependent inhibition of dendritic cell differentiation and downregulation of MHC-II, CD40, and CD86 on mature dendritic cells [38].…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culture mentioning
confidence: 99%
“…Previously, it was reported that various different sources of canine MSC modulate immune responses in vitro [12,[50][51][52][53][54]. In the study by Lee et al, which utilized canine bone marrow MSC, PGE2 was identified as the primary MSC factor that suppressed T cell proliferation [12,54].…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Lee et al, which utilized canine bone marrow MSC, PGE2 was identified as the primary MSC factor that suppressed T cell proliferation [12,54]. Kang et al identified PGE2 as an important T cell suppressive factor secreted by canine Ad-MSC, and also found that IDO production played an important role in T cell suppression [50]. Thus, the cyclooxygenase pathway appears to be a major pathway in canine MSC suppression, though relatively few other pathways have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The renal reparative manifestation of MSCs involves their anti-inflammatory functions [9,15]. Studies show that MSC can suppress macrophage trans-differentiation to inflammatory phenotypes [22], inhibit DC maturation and migration, and halt inflammatory cytokine generation from leukocytes [22][23][24]. HGF is immunoregulatory and reduces inflammatory cytokine generation from DCs [25].…”
Section: Introductionmentioning
confidence: 99%